Elementy konstytuujące proces ciągłego doskonalenia - Pewniak-Kaliska, Olga (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The main purpose of the paper is to present waste, the five S's, and standardization. These three activities are basic components of continuous improvement process. They are of great importance in organizing kaizen. They are irreplaceable in building lean organization and making easier rational management by leading to taking small steps. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1178, s. 100-115